62-kb Plasmids Harboring rulAB Homologues Confer UV-tolerance and Epiphytic Fitness to Pseudomonas syringae pv. syringae Mango Isolates. - Cazorla-López, Francisco Manuel; Codina, Juan C.; Abad, Cristina; Arrebola-Díez, Eva María; Torés, Juan Antonio; Murillo, Jesús; Pérez-García, Alejandro; De-Vicente-Moreno, Antonio (Springer, 2007)
The presence of genetic determinants homologous to rulAB genes for ultraviolet (UV) radiation resistance was determined in a collection of Pseudomonas syringae pv. syringae strains isolated from mango. The potential role of these plasmids in UV tolerance and ecological fitness in the mango phyllosphere was also evaluated. Nearly all of the 62-kb plasmids present in the P. syringae pv. syringae strains hybridized with a rulAB probe, but these 62-kb plasmids showed differences in restriction patterns. In vitro assays of tolerance to UV radiation of P. syringae pv. syringae strains showed a higher survival of the strains harboring the 62-kb plasmids compared to strains lacking plasmids when exposed to UVC or UVA+B fractions. Similar results were observed when transconjugants harboring the 62-kb plasmid were tested. Survival assays were carried out under field conditions, and a higher survival of P. syringae pv. syringae strains harboring 62-kb plasmids under direct solar radiation on the adaxial surface of leaves was also observed. When the assays were carried out in shady areas or on the abaxial surface of leaves, survival time was comparable for all the assayed strains, whether or not they contained a 62-kb plasmid hybridizing to rulAB. Our results indicate that P. syringae pv. syringae strains harboring 62-kb plasmids show an increase in ecological fitness when colonizing the mango phyllosphere.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/17415 --- https://link.springer.com/journal/248/how-to-publish-with-us
Keywords: Pseudomonas syringae; Plásmidos - Genética; Mangos - Resistencia a enfermedades y plagas; Pseudomonas; Ultravioleta; Plásmidos; Bacteria; Mango